Efisiensi distribusi pada bisnis komoditi rumput laut di Kabupaten Bombana - Harfin, Wa Ode Shafira; Lawelle, Sjamsu Alam; Mansyur, Akhmad; Sara, La; Riani, Irdam (Universitas Halu Oleo, 2023)
Seaweed distribution is the process of sending seaweed from producers to consumers. This study aimed to determine distribution, distribution patterns, and distribution efficiency in the seaweed commodity business. This research was conducted in Bombana Regency, from February to March 2022. Respondents were classified into 3 groups namely, seaweed farmers, small traders and big traders. Samples of each group were chosen purposively (purposive random sampling) the interview with each respondent used snowball sampling. The data collected includes the characteristics of the respondents, the characteristics of the seaweed business, and the minimum costs. The data were analyzed descriptively qualitative to answer the objective of how the distribution and pattern of distribution of seaweed in Bombana Regency was used, while the Least Cost method was used to answer the goal of seaweed distribution efficiency. The results showed that there were 4 seaweed distribution channels, namely: (1) seaweed farmers to small traders to big traders then to industry, (2) seaweed farmers to small traders to big traders then to exporters, (3) seaweed farmers to big traders then to industry, and (4) seaweed farmers to big traders then to the exporter. The amount of seaweed production distributed from seaweed farmers to small traders averaged 361.11 kg, while from small traders to wholesalers an averaged 3,817 kg, and from wholesalers to industry an average of 735 kg. The largest amount of seaweed production is from wholesalers to exporters with an average of 5,591 kg. The efficiency of distribution with the lowest cost occurs in distribution from seaweed farmers directly to big traders and from big traders to exporters